Advanced image processing with fusion and calcification enhancement in transcatheter aortic valve implantation: impact on radiation exposure. (23rd April 2018) - Overtchouk, Pavel; Sudre, Arnaud; Delhaye, Cédric; Juthier, Francis; Van Belle, Eric; Coisne, Augustin; Koussa, Mohamad; Mylotte, Darren; Modine, Thomas
Abstract: OBJECTIVES: Radiation exposure is a concern for both patients and operators during transcatheter aortic valve implantation (TAVI). Efforts to reduce radiation dose are warranted. We aimed at investigating if per-operative advanced image processing can reduce patient and operator irradiation use during TAVI. METHODS: We performed a prospective single-centre observational study comparing patient and operator radiation exposure using standard fluoroscopy (control group) or a novel technology of live advanced fluoroscopic image processing (test group) among consecutive patients undergoing TAVI between August 2015 and April 2016. Patient irradiation (dose–area product, effective dose and air kerma), contrast media volume and clinical outcomes were assessed. RESULTS: Among 152 elderly [median age (interquartile range): 83 (78–87)] patients ( n = 76 per group) undergoing TAVI, baseline clinical characteristics were similar between the control and test groups, except for a higher median EuroSCORE II (2.8% vs 2.3%, P = 0.02) and higher rate of TAVI for failing surgical bioprosthesis (11.8% vs 2.6%, P = 0.03) in the control group. The dose–area product was reduced in the test group: mean reduction of −27.5 Gy × cm 2 [95% confidence intervals (CIs): 15.9–39.1, P < 0.001]. Furthermore, effective dose [mean reduction −6.5 (95% CI: 5.9–7.2) mSv, P < 0.001] and air kerma [mean reduction −167.5 (95% CI 163.4–177.3) mGy, P < 0.001] were lower in the test group. Fluoroscopy time, contrast volume and clinical outcomes were similar. CONCLUSIONS: Patient radiation exposure was significantly reduced using a novel live advanced fluoroscopy image processing with calcification enhancement and fusion of the virtual aortic annulus without compromising patient safety.